Measuring internet addiction among multiracial youth in Malaysia - Omar, Siti Zobidah; Saharrudin, Nurul Farhana; Bolong, Jusang (Human Resource Management Academic Research Society, 2019)
Internet addiction among youths is a serious issue in Malaysia. Hence, this study aims to examine the level of internet addiction among multiracial youths in Malaysia. A total of 400 respondents was collected from the four main zones in Malaysia. The study concluded that several concerns have surfaced due to the impact from internet addiction, these multiracial youths perceived the internet to be an important part of their life, they felt left out without it, and they assumed that life is boring without the internet. Several recommendations are highlighted in light that it can be a basis for future planning in reducing internet addiction among future generations in Malaysia.